AKTIVITAS ANTIBAKTERI MADU HITAM PAHIT DAN MADU HITAM MANIS TERHADAP Escherichia coli dan Staphylococcus aureus - Sri Peni Fitrianingsih (JURNAL FARMASI GALENIKA, 2014)
Antibacterial activity of bitter-black honey and sweet-black honey against Escherichia coli and Staphylococcus aureus was investigated. The purpose of this study was to measure the antibacterial activity, Minimum Inhibition Concentration (MIC), and the action of bitter-black honey and sweet-black honey that collected from Borneo. Disc diffusion methode was used to measure the antibacterial activity and MIC of honeys. Turbidimetric assaywas used to measure the antibacterial action of honeys. Results showed that bitter-black honey and sweet-black honey possess antibacterial activity against E.coli and S.aureus. MIC value of bitter-black honey was 3,4%-3,8%. And MIC value of sweet-black honey was 4,4%-4,8%. Antibacterial action of two types of honey at concentration 6,25% against S.aureus was bacteriostatic. Bitter-black honey had higher antibacterial activity than sweet-black honey.